Classification of Crystallographic Data Using Canonical Correlation Analysis. (30th April 2007) - Ladisa Ladisa, M. M.; Lamura Lamura, A. A.; Laudadio Laudadio, T. T.
Abstract : A reliable and automatic method is applied to crystallographic data for tissue typing. The technique is based on canonical correlation analysis, a statistical method which makes use of the spectral-spatial information characterizing X-ray diffraction data measured from bone samples with implanted tissues. The performance has been compared with a standard crystallographic technique in terms of accuracy and automation. The proposed approach is able to provide reliable tissue classification with a direct tissue visualization without requiring any user interaction.